Understanding Financial Risk Dynamics: Systematic Literature Review inquiry into Credit, Market, and Operational Risks: (A Long-life Lesson From Global Perspective to Indonesia Market Financial Strategy) - Rizal S, Muh.; Siraj, Muhammad Luthfi; Syarifuddin, Syarifuddin; Tadampali, Andi Caezar To; Zainal, Henni; Mahmud, Ramlan (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This research delves into the intricate dynamics of financial risks—specifically credit, market, and operational risks—within the banking, investment, and corporate sectors, with a focus on both global and Indonesian contexts. By examining the key factors contributing to credit risk, the impact of global market volatility on financial stability, and the operational risks associated with the digital transformation of the financial sector, the study seeks to offer a comprehensive analysis that is both theoretically robust and practically relevant. This research employs a qualitative systematic literature review (SLR) to explore credit, market, and operational risks within the banking, investment, and corporate sectors, focusing on global and Indonesian contexts. The SLR process includes formulating research questions, identifying and screening relevant literature from databases like Scopus and Google Scholar, and synthesizing findings into key themes: credit risk dynamics, market volatility, operational risks in the digital age, and integrated risk management. This research provides a comprehensive analysis of financial risk management in the banking, investment, and corporate sectors, with a focus on Indonesia and global perspectives. The study reveals that digitalization has a significant impact on operational risk, enhancing efficiency but also increasing vulnerability to cybersecurity threats and disruptions. This underscores the need for robust risk management frameworks to address technology-driven challenges. The research also highlights the importance of improving risk disclosure transparency, which can positively influence credit risk management. Liquidity risk is identified as having a greater short-term impact on financial stability than credit risk, necessitating proactive liquidity management strategies. Technological innovations in finance are found to correlate with increased risks, including failures and cybersecurity threats, which must be carefully managed. The study examines the risks associated with platform-based financing models and the influence of global market volatility on investment strategies. In Indonesia, the banking sector faces distinct credit risk challenges due to high market concentration and systemic shocks, as well as operational risks from rapid digital transformation. The research emphasizes the necessity for Indonesian financial institutions to implement comprehensive cybersecurity measures, maintain resilient IT infrastructure, and utilize advanced monitoring tools to address these emerging risks. The study also stresses the importance of adopting integrated risk management frameworks that account for the interdependencies between credit, market, and operational risks in a globalized market.